Emotional Intelligence and Teaching Styles of Primary School Teachers - TIWARI, GAURANG; PANDEY, ASHA (THE PRIMARY TEACHER, 2014)
For studying teaching styles of teachers, teachers were categorised in four groups according to their level of Emotional Intelligence (EI) viz., Extremely High EI (EHE), high EI (HE), moderate EI (ME), and low EI (LE). By comparing and contrasting teaching styles of teachers of different groups, it was observed that teachers of EHE and HE groups were “INDIRECT” in their teaching styles and their counterparts were “DIRECT” in their teaching styles. In addition, constructivist compatible elements were observed to be embedded in teaching styles of teachers of EHE and HE groups than their counterparts.